ANALISIS PENERAPAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT PADA LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI DALAM FITUR PEMBAYARAN PAYLATER - Tasya Hanifah Anggraini; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
The presence of electronic transactions in the payment system plays a big role for both business actors and consumers in conducting transaction activities. Currently there is a payment feature that supports consumers to shop by using installment payments or providing credit without giving credit and providing guarantees (Paylater). As the name implies, the Paylater feature provides an opportunity for consumers to take advantage of services and services while they pay at the end according to the given limit. One of the e-commerce that offers payment method features with buy now, pay later or Paylater is the Shopee Platform. Shopee makes it easy by providing easy requirements to activate this Shopee Paylater account. However, on the other hand, the convenience provided actually creates a problem, where consumers can easily get credit with large limits without many requirements. This study examines how the application of the prudential principle in the Shopee Paylater payment feature in reducing the risk of default.